TREATMENT-FREE RESPONSE USING BRAZILIAN IMATINIB COPIES AS FIRST LINE -RESULTS FROM TWO PROSPECTIVE CLINICAL TRIALS - RT Centrone; FS Seguro; M Bellesso; L Nardinelli; I Bendit; A Alves; V Rocha (2022)
Several trials have demonstrated the feasibility of tyrosine kinase inhibitors (TKI) treatment in chronic myeloid leukemia (CML) patients with a deep molecular response, but little data is available about the results using imatinib copies. Brazil has been using imatinib copies as a first-line treatment since 2013. To report the results of two Brazilian imatinib copies trials and to evaluate factors impacting treatment-free remission (TFR) and treatment-free survival (TFS) after imatinib discontinuation. From Dec-2016 until Oct-2018 (USP trial, NCT03239886) and from Oct-2020 until Apr-2021(Hemomed Trial- DIP), 51 eligible patients were included to participate in two trials of imatinib discontinuation. Inclusion criteria: age > 18 years, chronic phase, minimum of three years (USP trial) and four years (DIP) of imatinib copies therapy, a deep molecular response, defined as MR4.0 or MR4.5 sustained for more than 2 years, and a confirmatory test at the moment of the screening. Atypical transcripts were excluded. After discontinuation, patients on the USP trial were monitored by Q-PCR monthly for the first 6 months and bimonthly after 6 months for the first year and quarterly afterwards. Patients in DIP monitoring were monthly for the first year and every 2 months in the second year. Minimal criteria for IM re-initiation was loss of major molecular response (MMR) confirmed by two exams. Median age was 53 years at the time of discontinuation. 58% male (USP) and 65% female (DIP). Imatinibs therapy was 9.9 years (3-15.5 y). 52.9% had MR4.5 at the screening. TFS at 6 months was 78% (95 Cl 67-90), 12 months 66% (95 Cl 54-80) and at 24 months 54% (95 Cl 42-71). TFS by center at 12 months were 64.5 % (USP) and 67% (DIP). TFS according to previous molecular response after 24 months of follow-up (MR4 vs. MR4.5) (p =0,086). MMR recovery was present in 100% with a median time of 3.5 months. Four patients are still on TFR because the double testing of MMR loss was not confirmed. These two trials demonstrated the feasibility and safety of imatinib discontinuation, even using Brazilian copies, and the results were similar to that presented in another trial. The confirmatory exam to establish the loss of TFR was useful and safe. However, the results no suggest a benefit on monthly Q-PCR after six months of follow-up.